Single cut distal femoral osteotomy for correction of femoral torsion and valgus malformity in patellofemoral malalignment - proof of application of new trigonometrical calculations and 3D-printed cutting guides - Florian B. Imhoff; Joscha Schnell; Alejandro Magaña; Theresa Diermeier; Bastian Scheiderer; Sepp Braun; Andreas B. Imhoff; Robert A. Arciero; Knut Beitzel (BMC Musculoskeletal Disorders, 2018)
Abstract Background The purpose of this study was to perform a derotational osteotomy at the distal femur, as is done in cases of patellofemoral instability, and demonstrate the predictability of three-dimensional (3D) changes on axes in a cadaveric model by the use of a new mathematical approach. Methods Ten human cadaveric femurs, with increased antetorsion, underwent a visually observed derotational osteotomy at the distal femur by 20°, as is commonly done in clinics. For surgery, a single cut osteotomy with a defined cutting angle was calculated and given using a simple 3D-printed cutting guide per specimen, based on a newly-created trigonometrical model. To simulate post-operative straight frontal alignment in a normal range, a goal for the mechanical lateral distal femur angle (mLDFA) was set to 87.0° for five specimens (87-goal group) and 90.0° for five specimens (90-goal group). Specimens underwent pre- and post-operative radiographic analysis with CT scan for torsion and frontal plane x-ray for alignment measurements of mLDFA and anatomical mechanical angle (AMA). Results Performed derotation showed a mean of 19.69° ±1.08°SD (95% CI: 18.91° to 20.47°). Regarding frontal alignment, a mean mLDFA of 86.9° ±0.66°SD (87-goal-group) and 90.42° ±0.25° SD (90-goal group), was observed (p = 0.008). Overall, the mean difference between intended mLDFA-goal and post-operatively achieved mLDFA was 0.14° ±0.56° SD (95% CI: -0.26° to 0.54°). Conclusion A preoperative calculated angle for single cut derotational osteotomy at the distal femur leads to a clinically precise post-operative result on torsion and frontal alignment when using this approach.